2016
DOI: 10.3892/ol.2016.4263
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and practical method to detect the T790M mutation in the epidermal growth factor receptor

Abstract: Abstract. The current study aimed to develop a method to rapidly, sensitively and practically screen for the epidermal growth factor receptor (EGFR) T790M mutation. This method combines an allele-specific competitive blocker (ACB) with a TaqMan quantitative polymerase chain reaction (PCR) amplification refractory mutation system (ARMS) in a one-step reaction. Using a mimic of a human genomic DNA panel containing serially diluted mutant alleles, the performance efficacy of this method was assessed. Using this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…Importantly, Costa et al [32] also demonstrated that EGFR T790M status does not influence PFS in patients receiving chemotherapy. In contrast to other studies [30,31,32,34,44,45], Fujita et al [26] reported a trend towards increased duration of response to TKI in T790M-mutated patients. Although the results of meta-analyses support the predictive role of mosaic T790M mutation in determining TKI response, it is necessary to acknowledge that the frequency of the T790M detection in the mentioned studies ranged from 22% to 80% [33,47,48].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Importantly, Costa et al [32] also demonstrated that EGFR T790M status does not influence PFS in patients receiving chemotherapy. In contrast to other studies [30,31,32,34,44,45], Fujita et al [26] reported a trend towards increased duration of response to TKI in T790M-mutated patients. Although the results of meta-analyses support the predictive role of mosaic T790M mutation in determining TKI response, it is necessary to acknowledge that the frequency of the T790M detection in the mentioned studies ranged from 22% to 80% [33,47,48].…”
Section: Discussioncontrasting
confidence: 50%
“…Although the results of meta-analyses support the predictive role of mosaic T790M mutation in determining TKI response, it is necessary to acknowledge that the frequency of the T790M detection in the mentioned studies ranged from 22% to 80% [33,47,48]. Furthermore, given that highly sensitive detection of mosaic T790M allele and collection of EGFR-mutated patients with sufficient treatment follow-up are challenging, the majority of available clinical studies are of modest size [31,32,44,45]. There could also be a publication bias, as small investigations reporting ‘positive' results have better chances to be reported than the ‘negative' ones [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have also explored the relationship between prognosis and pretreatment T790M mutation 2532. Increasing evidence has indicated that T790M may exist at a low frequency within the tumor cells before EGFR-TKI treatment and may become the dominant clone only after drug selection pressure of EGFR-TKI treatment 25.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has indicated that T790M may exist at a low frequency within the tumor cells before EGFR-TKI treatment and may become the dominant clone only after drug selection pressure of EGFR-TKI treatment 25. Although reliable and widely accepted methods for detecting EGFR T790M mutation status have not yet been established, some researchers have attempted to detect T790M mutation before EGFR-TKI treatment using different assays with sensitivities ranging from 0.001% to 0.4% 2532. This meta-analysis explored the influences of acquired T790M mutation following EGFR-TKI treatment and de novo T790M mutation prior to EGFR-TKI treatment on survival and prognosis in patients with advanced NSCLC who had activating EGFR mutations.…”
Section: Introductionmentioning
confidence: 99%